1999
DOI: 10.3109/13645709909153128
|View full text |Cite
|
Sign up to set email alerts
|

Rigid endoscopy in minimally invasive therapy of tumours of the paranasal sinuses and skull base

Abstract: The use of rigid endoscopes in paranasal sinuses, nasopharynx and skull base surgery has extended and diversified, specifically for the treatment of malignant lesions of the nose and paranasal sinuses. We have endoscopically treated 33 patients with tumours of the skull base, paranasal sinuses and nasopharynx during the last 8 years (five patients with juvenile nasopharyngeal angiofibromas and 28 patients with various malignant tumours and T-classification). Endoscopic tumour surgery can be performed in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…24 This single center study from the Medical University in Graz, Austria, which builds on the authors' prior reports, 9,22,25,26 described 14 patients with esthesioneuroblastoma. Twelve patients had newly diagnosed disease and two had previously undergone surgery.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…24 This single center study from the Medical University in Graz, Austria, which builds on the authors' prior reports, 9,22,25,26 described 14 patients with esthesioneuroblastoma. Twelve patients had newly diagnosed disease and two had previously undergone surgery.…”
Section: Discussionmentioning
confidence: 96%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] To our knowledge, Folbe et al is the largest series reported. 16 This was a combined series from the University of Pittsburgh Medical Center and the University of Miami Miller School of Medicine and builds on the authors' previous experience.…”
Section: Discussionmentioning
confidence: 98%
“…Combining technical advances of instrumentation, imaging, and interventional radiology, angiofibromas stage 1 and 2 seem to be suitable for endonasal removal [10,17,18]. This was also experienced in our study.…”
Section: Discussionmentioning
confidence: 50%
“…Growing experience has led to extending indications for endonasal approaches of benign and malignant tumors [1,[5][6][7][8][9][10]. The aim of our study was to detail our experience with various tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation